2019
DOI: 10.1149/2.1241915jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fast Charging and Reduced Lithium-Plating by Laser-Structured Anodes for Lithium-Ion Batteries

Abstract: Within this paper we report on a lithium-ion battery with laser-structured graphite anodes, alleviating current drawbacks of lithiumion batteries such as the reduced discharge capacity at high Crates and the onset of lithium-plating during fast charging. These issues are intensified at low temperatures, as reaction and diffusion kinetics decelerate, which is why a focus of the presented work lies on low temperature performance. Electrochemical impedance spectroscopy was used to show a reduction in the impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…
out on the graphite anode surface under fast-charging conditions in high-energydensity cells. The irreversibility associated with Li plating leads to permanent loss of Li from the accessible reservoir and capacity fade, which is the key challenge that limits fast-charging of LIBs.Strategies to prevent and/or mitigate the impacts of Li plating on graphite have drawn great interest in recent years, including: 1) alternative anode materials such as lithium titanate, [6] titanium niobate, [7] and hybrid mixtures of hard carbon with graphite; [5] 2) modifying the electrode architecture to facilitate enhanced mass transport; [8][9][10][11][12] 3) asymmetric temperature modulation; [13] 4) surface coatings to modify interface behavior; [14][15][16][17] and 5) electrolyte modifications to increase
…”
mentioning
confidence: 99%
“…
out on the graphite anode surface under fast-charging conditions in high-energydensity cells. The irreversibility associated with Li plating leads to permanent loss of Li from the accessible reservoir and capacity fade, which is the key challenge that limits fast-charging of LIBs.Strategies to prevent and/or mitigate the impacts of Li plating on graphite have drawn great interest in recent years, including: 1) alternative anode materials such as lithium titanate, [6] titanium niobate, [7] and hybrid mixtures of hard carbon with graphite; [5] 2) modifying the electrode architecture to facilitate enhanced mass transport; [8][9][10][11][12] 3) asymmetric temperature modulation; [13] 4) surface coatings to modify interface behavior; [14][15][16][17] and 5) electrolyte modifications to increase
…”
mentioning
confidence: 99%
“…All Li observed in the post‐mortem analyses are either isolated (dead) Li or those in the regions where the electrolyte is completely depleted. The results obtained from non‐destructive methods, such as those by analyzing the change in voltage or differential voltage during post‐charging relaxation, and those by observing the change in capacity or differential capacity in the subsequent discharge, are changed with rest time due to the issue that the plated Li chemically re‐intercalates into graphite.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
“…In this regard, reducing the thickness (accordingly the loading) and tortuosity of graphite anode is shown to be effective in facilitating ion transport in the electrode, and hence mitigate Li plating . The graphite anode with low tortuosity, such as those made by laser cutting and freeze‐casting, is shown to offer much improved rate capability and reduced Li plating. Another strategy is to enhance the kinetics of the electrode reactions by raising the temperature of the charging process.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cabin heating, the decreased performance of the vehicle's battery at low temperatures also affects a BEV's driving range. Cold conditions cause declined reactivity and diminished ionic conductivity in Li-ion cells [15,21], which affects their usable capacity [22] and impedance [23]. In this context, Nagasubramanian et al [24] showed that under extreme cold conditions (−40 • C) a Li-ion cell can lose up to 95% of its energy and more than 98% of its power capability compared to performance levels at 25 • C. Similar research shows that a cell's capacity can drop by up to 23% at −20 • C compared to the capacity at 25 • C [25].…”
Section: Introductionmentioning
confidence: 99%